THE EVALUATION OF ELECTRONIC HEALTH RECORD ADOPTION AMONG HEALTH PROFESSIONALS IN HOSPITAL SETTING - Septiani, Riza; Mairani, Tiara (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2021)
Background: Electronic Health Record (EHR) utilization has been improved nowadays and it is believed that the adoption of Information Technology (IT) that has been implemented in various setting may also accelerate qualified implementation in health care setting. This study aimed to evaluate EHR utilization in various settings by systemic literature review. Methods: systemic literature research was conducted with keywords (evaluat* model OR evaluat* framework) AND (health professional* OR health staff*) AND (electronic health record OR EHR) AND (us* OR engagement OR implementation OR adoption) AND hospital. Result: 833 literatures found at the beginning of literature search, after apply limitations, remove duplicates and exclude of irrelevant literatures, finally total 7 articles were included in the review. Conclusion: there are benefits and drawbacks of EHR utilization among health professional in different healthcare settings in some countries that included in this review. Some health professionals had positive experience of using EHR that its use can improve clinicians involvement, better clinicians representation and decrease workload. Meanwhile, others had different views that EHR use are ineffectiveness due to inability of the systems to meet users need, poor integration with existing workflows, poor IT skills among users and limited resources and training of EHR. Recommendation: Therefore, it is important to improve better design of EHR system with customized functionalities so it could improve the implementation and adoption of EHR by health professionals as end user.